2022
DOI: 10.1002/jso.26925
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery for local recurrence after sublobar surgery in Stages I and II non‐small cell lung cancer

Abstract: Background and Objectives: To examine if patients undergoing salvage surgery for local recurrence following sublobar resection (SLR) have similar perioperative complications and overall survival (OS) compared to lobectomy patients for early stage non-small cell lung cancer (NSCLC).Methods: Patients undergoing lobectomy and SLR (segmentectomy or wedge resection) for Stages I and II NSCLC from 2010 to 2016 were reviewed. Lobectomy patients and those who underwent salvage surgery for local recurrence after SLR we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The efficacy and safety of salvage thoracic operations have not yet been fully elucidated [ 17 ]. The present definition of salvage surgery for lung cancer is younger than 20 years and refers almost exclusively to non-small cell lung cancer (NSCLC) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], but it is important to underline that the same definition was proposed for and the same procedures were performed in SCLC, as presented above; therefore, the theoretical and practical information is resumed as follows: Salvage surgery for an emergent complication, as a life-saving procedure, performed for an event that occurred during the natural history of the tumor or as a complication during oncological treatment, including SBRT, with curative or palliative intent: massive hemoptysis, lung abscess, empyema, broncho–pleural fistula; Salvage surgery after definitive (full-dose) chemo–radiation therapy/after previous local (SABR) or general treatment (ex. targeted therapy): residual/persistent localized disease, relapsed tumor/recurrence after complete response, cases judged to be contraindicated for chemotherapy or definite radiation therapy due to severe comorbidities, despite a clinical diagnosis of NSCLC stage IIIA, IIIB, or IV disease initially, delayed decision to convert to a trimodal approach; Salvage surgery for progression under chemotherapy; Salvage surgery for oligo-metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of salvage thoracic operations have not yet been fully elucidated [ 17 ]. The present definition of salvage surgery for lung cancer is younger than 20 years and refers almost exclusively to non-small cell lung cancer (NSCLC) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], but it is important to underline that the same definition was proposed for and the same procedures were performed in SCLC, as presented above; therefore, the theoretical and practical information is resumed as follows: Salvage surgery for an emergent complication, as a life-saving procedure, performed for an event that occurred during the natural history of the tumor or as a complication during oncological treatment, including SBRT, with curative or palliative intent: massive hemoptysis, lung abscess, empyema, broncho–pleural fistula; Salvage surgery after definitive (full-dose) chemo–radiation therapy/after previous local (SABR) or general treatment (ex. targeted therapy): residual/persistent localized disease, relapsed tumor/recurrence after complete response, cases judged to be contraindicated for chemotherapy or definite radiation therapy due to severe comorbidities, despite a clinical diagnosis of NSCLC stage IIIA, IIIB, or IV disease initially, delayed decision to convert to a trimodal approach; Salvage surgery for progression under chemotherapy; Salvage surgery for oligo-metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…While it was found that reoperative therapy was safe and technically feasible, only 25% of potentially salvageable patients made it to reoperative salvage surgery, with a whole host of factors contributing. 49 So while sublobar resection is a parenchymal-sparing strategy that may allow for recurrences to be further treated surgically, the fact of the matter seems most patients will not get there. Additionally, the JCOG study found both ipsilateral and contralateral mediastinal nodal recurrences were higher with segmentectomy, something reoperative surgery can do little to address, no matter how small the incisions or how quick the recovery is.…”
Section: Evolving Datamentioning
confidence: 99%
“…Take, for instance, a review from this institution, which evaluated salvage surgery for recurrence after initial sublobar resection. While it was found that reoperative therapy was safe and technically feasible, only 25% of potentially salvageable patients made it to reoperative salvage surgery, with a whole host of factors contributing 49 . So while sublobar resection is a parenchymal‐sparing strategy that may allow for recurrences to be further treated surgically, the fact of the matter seems most patients will not get there.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection remains the primary treatment for non‐small cell lung cancer (NSCLC), but some patients still experience distant metastasis and recurrence postoperatively. This poor outcome may be attributed to the presence of residual micrometastases or subclinical lesions 1,2 . In many patients with NSCLC, local therapies alone are insufficient to prevent recurrence, underscoring the need for perioperative treatments to improve NSCLC outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This poor outcome may be attributed to the presence of residual micrometastases or subclinical lesions. 1 , 2 In many patients with NSCLC, local therapies alone are insufficient to prevent recurrence, underscoring the need for perioperative treatments to improve NSCLC outcomes. Neoadjuvant chemotherapy administered before definitive local radiotherapy or surgery aims to shrink primary tumors, eradicate subclinical lesions, facilitate subsequent therapies, and improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%